HOW SOCIAL MEDIA CAN HELP IN LEARNING ENGLISH LANGUAGE (Modern education and development, 2024)
In the digital age, social media has become a powerful tool for language learning, offering numerous benefits for English learners. This article explores how social media platforms can help individuals improve their English language skills through real-world language exposure, interactive communities, visual content, and daily practice. By engaging with native speakers, following educational accounts, and participating in language challenges, learners can enhance their vocabulary, grammar, pronunciation, and cultural understanding. The flexibility and accessibility of social media make it an invaluable resource for both beginners and advanced learners seeking to practice English in a dynamic and enjoyable way.